Preparing for Industry 4.0 and Digital Transformations In SMEs. European and National Aspects - Moraliyska, Monika; Antonova, Albena (UNWE Yearbook, 2018)
The objectives of the research are to explore the new technological, organizational and institutional changes leading to the implementation of models of Industry 4.0 into SMEs. The methodology includes a theoretical investigation of the industrial revolutions and current digital transformation processes, comparative studies of the EU policy efforts and national initiatives, as well as empirical research - in-depth interviews with companies in Bulgaria. The results include conclusions based on empirical data gathered within the DIGITRANS INTERREG project concerning the digital readiness of the Bulgarian SMEs.